Examination and possible interpretations of a Middle Bronze Age structured deposition - Gucsi, László; Szabó, Nóra (Dissertationes Archaeologicae, 2019)
Ceramic depositions occur frequently in the Bronze Age throughout the Carpathian Basin, however, their characteristics and composition can vary between periods, cultures and regions. Thus there could be many theories and interpretations offered for the reasons behind hiding these depots. At the site of Budajenő, Hegyiszántók a structured deposition dating to the final phase of the Middle Bronze Age came to light, which is not only unique in terms of the quantity of the vessels but also of their quality, both on an intra-site level and from the perspective of the Hungarian Middle Bronze Age. The aim of this paper is to present a complex and multi-faceted analysis, which helps not only to understand the possible reasons behind the concealment of the vessels, but also to offer an interpretation for the chain of events in which they could have played a central role. Besides the examination of the quantity and the cultural characteristics of the vessels, traces of use-wear, along with the phenomena of secondary burning and deliberate fragmentations are also discussed.